Engineering design project : series 2 - Hassan, Mohd Fahrul (Penerbit UTHM, 2017)
This book is a compilation of engineering design projects which illustrates a detail explanation on the design process including all tools and methods involved in each design stage. The presented projects have been selected to prepare engineering students with the adequate knowledge and skills required in organizing product based project, formulating problems, generating and evaluating alternatives, preparing technical documentation and considering the sustainable and economic constraints for the product development and realization stage using the integration of various disciplines in mechanical and manufacturing engineering. This book is generally suitable as a reference to project-oriented problem-based learning (POPBL) activities at engineering institutions.